Wide-Field Fluorescence Microscopy of Real-Time Bioconjugation Sensing - Marcin Szalkowski; Karolina Sulowska; Justyna Grzelak; Joanna Niedziółka-Jönsson; Ewa Roźniecka; Dorota Kowalska; Sebastian Maćkowski (Sensors, 2018)
We apply wide-field fluorescence microscopy to measure real-time attachment of photosynthetic proteins to plasmonically active silver nanowires. The observation of this effect is enabled, on the one hand, by sensitive detection of fluorescence and, on the other hand, by plasmonic enhancement of protein fluorescence. We examined two sample configurations with substrates being a bare glass coverslip and a coverslip functionalized with a monolayer of streptavidin. The different preparation of the substrate changes the observed behavior as far as attachment of the protein is concerned as well as its subsequent photobleaching. For the latter substrate the conjugation process is measurably slower. The described method can be universally applied in studying protein-nanostructure interactions for real-time fluorescence-based sensing.